Gen-Z Marketing Strategies: Understanding Consumer Preferences and Building Sustainable Relationships - Salam, Karta Negara; Singkeruang, A. We Tenri Fatimah; Husni, M. Fahrul; Baharuddin, B.; A.R, Dhita Pratiwi (Golden Ratio of Mapping Idea and Literature Format, 2024)
In the contemporary digital landscape, marketing strategies have become increasingly intricate due to the influence of Generation Z, a significant consumer group born between the mid-1990s and the early 2010s. This generation, labeled as "digital natives," presents unique challenges and opportunities for marketers, given their adeptness with technology and distinct shopping behaviors. To address these challenges, this research aims to conduct a thorough analysis of Generation Z's consumer preferences and effective marketing strategies for building sustainable relationships with them. Drawing from a multitude of qualitative studies spanning from 2010 to 2024, this study employs a systematic review approach to extract insights into Generation Z's preferences and behaviors. By synthesizing qualitative data and employing thematic analysis, the research uncovers recurring patterns, emerging trends, and socio-cultural influences shaping Generation Z's consumer behavior. Furthermore, the study explores the shift in preferences from physical products to experiences and the added value provided by brands. Key findings highlight Generation Z's inclination towards brands prioritizing social values, environmental concerns, and sustainability, as well as their reliance on social media influencers and preference for personalized experiences. The insights gleaned from this research are expected to provide valuable guidance for companies seeking to tailor their marketing strategies to effectively engage and resonate with Generation Z, thereby remaining competitive in the dynamic consumer market.